SISTEM PAKAR DIAGNOSIS HAMA DAN PENYAKIT PADA TANAMAN KANGKUNG MENGGUNAKAN METODE FORWARD CHAINING - Nasrulloh, Iffan Ahmad; Raharja, Pradana Ananda; Arifa, Amalia Beladinna (STMIK Palangkaraya, 2022)
The production of water spinach vegetable crops in 2020 in Central Java ranks 2nd in water spinach production, which is 29,108 tons. The amount of water in spinach production and the increased risk of being attacked by pests and diseases will be even more significant, and proper care is needed to improve the quality of water spinach. It takes an expert to convey knowledge about controlling pests and diseases that are good and right. From these problems, we developed a system to overcome the problem of water spinach plant disease. This expert system uses the forward chaining method. The results of this study are a pest and disease diagnosis system on water spinach using a website-based forward chaining method with accuracy testing using the confusion matrix method by testing 50 rules. Of 50 data, 45 are considered appropriate, and the results of 5 rules are not relevant, so the evaluation results of this expert system produce system accuracy with a percentage of 90%.